Evaluation of water quality through physical–chemical variables and eutrophication indicators in the Apanás – Asturias Hydroelectric Reservoir, (RAMSAR, No. 1137), Jinotega - Caballero Arbizú, Yader Santiago (Torreon Universitario Magazine, 2023)
The reservoirs built for hydroelectric plants, in addition to providing energy, are also reservoirs of water for human and animal consumption, and irrigation in crops, for this reason, it is important to evaluate the quality of these waters periodically. In this study, the water quality of the Apanás-Asturias reservoir was evaluated using physical, chemical, and microbiological parameters and nutrients that indicate eutrophication. Samples were taken at three points of the reservoir: WWTP-Las Flores, Central Point, and Apanás-Asturias Connection on Sep-19 and Sep-20. The results obtained from the physical-chemical analyses showed that the water of the reservoir is of good quality, except for turbidity, true color, and iron. The concentrations of dissolved oxygen at the three points sampled in the Apanás-Asturias Reservoir were above the limit established by the Nicaraguan Technical Standard for the classification of Water Resources (NTON, 2000) for waters intended for navigation and electricity generation (> 3.0 mg.l-1). Fe at all sampled sites were found above the maximum allowable value under the Canadian Environmental Protection Standards (0.3 mg.l-1) and above the Irrigation Standards (5 mg.l-1). On the other hand, the microbiological results showed high concentrations of fecal contamination indicators in Sept-2019, especially at the WWTP-Las Flores Point in the Apanás-Asturias reservoir. The trophic state of the waters of the Apanás-Asturias reservoir in the WWTP-Las Flores and Punto Central sites is eutrophic in Sep-19 and Sep-20, while in the Apanás-Asturias connection site the trophic state is Mesotrophic based on chlorophyll a and total phosphorus.